“Eficacia de las Movilizaciones Neuromeníngeas del Nervio Ciático en Pacientes con Afecciones de Región Lumbar que acuden al área de Fisioterapia en la Unidad De Atención Ambulatoria Del IESS Nº 309 de la Ciudad Sucúa Provincia De Morona Santiago en el Período Octubre 2015 a Marzo 2016” - Borja Leon, Junior Gustavo (2016)
". Neuromeningeal mobilization technique is a method of body mechanics which will directly or indirectly influence the mechanical and mecanosensitico system, applying this technique decreases the degree of pain in patients suffering from low back pain conditions. During data collection method to develop the research was qualitative and descriptive, which will detail in later chapters. As a result of this study show that the United Ambulatory IESS No. 309 in the city of Sucúa a considerable amount of patients approached during the period of the months of October to March that was our investigative period, in total there were 35 patients with back pain condition, data were collected through medical records. Tabulations obtained we show that in patients by 54% at the end of treatment Mobilisations neuromeningeal presented a degree of mild pain. Among the conclusions it was evident that those who their received from 16 to 20 sessions are located on the degree of pain from 8 to 9 (very severe pain) treatment was very beneficial since this number of people decreased their level of pain from 0 to 1 (no pain) rejoining their daily work and thus bringing better physical activity.